Into the groove - Hurley, Andrew Wright (Boydell & Brewer, 2015)
In Germany between the mid-1990s and the mid-2000s there was an unprecedented 'confusion of the spheres' of literature and popular music. Popular musicians 'crossed over' into the literary field, editors and writers called for contemporary German literature to become more like popular music, writers attempted to borrow structural aspects from music or paid new attention to popular music at the thematic level. Others sought to raise their profiles by means of performance models taken from the popular music field. This book sets out to make sense of this situation. It argues for more inclusive and detailed attention to what it calls 'musico-centric fiction', for which it discerns intellectual precursors going back to the 1960s and also identifies examples written since the turn of the millennium, after the would-be death of 'pop literature'. In doing so, it focuses on fiction and paratextual interventions by authors including Peter Handke, Rolf Dieter Brinkmann, Rainald Goetz, Andreas Neumeister, Thomas Meinecke, Matthias Politycki, Frank Goosen, Benjamin von Stuckrad-Barre, Thomas Brussig, Karen Duve, and Kerstin Grether. Andrew W. Hurley is Senior Lecturer in German and Cultural Studies at the University of Technology, Sydney, Australia.
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Deutsch; Roman; Unterhaltungsmusik; Literatur; Popmusik; Musik; Popliteratur